Narrativas de adolescentes y sus familias: factores de riesgo y factores protectivos presentes en su contexto más allá del dato. - Narváez Zurita, Margarita Alexandra (2014)
This investigation wasmading in a qualitative ethnographic way, this investigation started by the needs and emergency topics about the teenagersenvironment. Though the individual interviews and group dialogues with as teenagers students that get alcohol and another that not, plus a group of parents, we can establish some dangerous social situations that influence of the teenagers who take out alcohol, protection factors about the alcohol getting in this human group, as the alcohol getting in the family practices and family socialization that prevent the alcohol getting, when these categories will be recognize, they can be establish with their trends.